(untitled) (The 40th International Pupils’ Attitudes Towards Technology Conference Proceedings 2023, 2023)
In 2022, South Korea announced new national curriculum that implement it from 2023. High school curriculum is about to fully implement the high school credit system, which allows students to choose subjects that suit their needs and career paths. In South Korea, technology education in middle school is a common compulsory subject, but high school technology education is a selective subject and has the name of technology and home-economics. High school technology education experiences difficulties that are not selected in many schools due to the confusion of identity of subject names and social negative perception of technology. The purpose of this is to develop an engineering education program that can be used in high school technology education and to verify its effect on students. To achieve the purpose of this study, an engineering education program was developed and students’ changes through the program were measured. This study was based on a single-group pre-post test design and was conducted with 96 10th grade students. As a result of this study, students’ engineering interest, engineering self-efficacy, and engineering career awareness were statistically significantly improved through the developed engineering education program. This study provides great implications for actively including and utilizing engineering in technology education. In addition, it will give great implication for the direction and program development of high school technology education.